A high prevalence of abnormal personality traits in chronic users of anabolic-androgenic steroids. Issue 3 (September 1996) - Cooper, C J; Noakes, T D; Dunne, T; Lambert, M I; Rochford, K
Abstract : OBJECTIVE: (1) To assess the personality profiles of the anabolic androgenic steroid users (AAS) and (2) to determine whether valid premorbid personality traits could be obtained from cross sectional assessment using multisource data. METHODS: The first author became a participant-observer in a group of body builders. An experimental group of body builders who had been using AAS for no more than 18 months (n = 12) was identified. A group of control subjects, each of whom claimed that he did not, and never had, used AAS (n = 12) was also recruited during this period. Key informants played a crucial role in recruiting subjects representative of the AAS and body building communities. An interview schedule based on the Diagnostic and statistical manual of mental disorders (DSM3-R) personality disorder criteria was conducted with each subject. Additional data were obtained from an AAS using informant and significant others including family and friends. RESULTS: The user group was significantly heavier than the control group and showed abnormal personality traits, in contrast to the control group. Personality traits of AAS users before the onset of AAS use, assessed retrospectively, were not different from personality traits of control subjects. There were significant differences between the before and after personality traits in AAS user group. CONCLUSIONS: The results suggest (1) that AAS use is associated with significant disturbances in personality profile, and (2) that these personality disturbances are possibly the direct result of AAS use.